1989
DOI: 10.1530/jrf.0.0860335
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization patterns in anterior vaginal fluid from bitches in oestrus

Abstract: Bitches exhibited a characteristic arborization pattern of the fluid from the anterior vagina during pro-oestrus and oestrus. These changes were monitored together with conventional vaginal cytology and plasma oestrogen and progestagen concentrations. A classical ferning pattern, similar to that seen in bovine cervical mucus at oestrus, occurred after the peak in plasma oestrogen concentrations. Ferning was most intense after the second peak of cornification of vaginal epithelial cells. It is suggested that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
1
15
0
2
Order By: Relevance
“…However, cervicovaginal mucus arborisation was identified in all bitches during the study. Its occurrence and appearance was similar to that previously reported (England and Allen 1989a) although 'in several bitches the ferning index was lower than these authors claimed and sporadic ferning was identified during early proestrus in nine bitches. The mean interval between the calculated LH surge and the peak of ferning (or the midpoint of the ferning plateau) was 2.3 t 2.1 days.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, cervicovaginal mucus arborisation was identified in all bitches during the study. Its occurrence and appearance was similar to that previously reported (England and Allen 1989a) although 'in several bitches the ferning index was lower than these authors claimed and sporadic ferning was identified during early proestrus in nine bitches. The mean interval between the calculated LH surge and the peak of ferning (or the midpoint of the ferning plateau) was 2.3 t 2.1 days.…”
Section: Discussionsupporting
confidence: 89%
“…Allen (1985) noted that polymorphonuclear leucocytes may be found throughout the entire oestral period; the extent of these variations has not been quantified. Crystallisation of mucus collected from the anterior vagina has been described in the bitch, occurring after the peak of plasma oestrogen concentration (England and Allen 1989a). These workers suggested that an assessment of the fern type and amount combined with vaginal cytology could be used to determine the optimal mating time.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods has been proposed to monitor the bitch oestrous cycle, such as serial reading of the electrical resistance of the vaginal mucus around the time of ovulation, using probes inserted into the vagina during the heat period (Fontbonne, 2008), or the crystallization patterns in anterior vaginal fluids (England & Allen, 1989) or in saliva (Pardo-Carmona et al, 2010), which have been found up not to present an acceptable reliabily in the identification of the canine ovulation. …”
Section: Proposed Alternative Methodsmentioning
confidence: 99%
“…Furthermore, oestrogens induce the growth and keratinisation of the vaginal epithelium. A slight rise in plasma P4 levels occurs from the beginning of pro‐oestrus to the end of oestrus; levels start to increase with regard to baseline values approximately 2 days before ovulation, during the LH surge (England and Allen 1989). Ovulation occurs when P4 concentrations are between 2 and 10 ng/ml (Bouchard and others 1991, Kutzler and others 2003, Chapwanya and others 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Using these properties, commercial tests have been developed to enable women to establish their fertile period (FP) quickly, easily and cheaply. Although the crystallisation of cervical and vaginal mucus has been investigated in many species, including dogs and human beings (Betteridge and Raeside 1962, England and Allen 1989, England 1992, Pattanasuttinont and others 2007, Jezkova and others 2008), there are no previous reports on the use of saliva as an indicator of the FP in bitches.…”
Section: Introductionmentioning
confidence: 99%